Developing a Self-Study E-Module for English Medical Terminology: A Need Analysis of Health Science Students - Rohmah, Farida Noor (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
Mastery in English medical terminology is crucial for health science students to engage with academic material, comprehend clinical information, and communicate successfully in professional settings. Many learners have ongoing challenges due to the lack of specialized, self-directed learning tools designed for their specific discipline and contextual requirements. This study performed the needs analysis phase of the ADDIE instructional design paradigm to examine the unique requirements for a self-learning e-module in English medical terminology. Data were gathered from 64 students participating in nursing, midwifery, and medical programs via a validated online questionnaire and semi-structured interviews with two faculty lecturers. The analysis investigated three dimensions: learners' needs, existing shortcomings, and favored learning modalities. The findings indicated that students necessitate terminology proficiency mainly for comprehending lectures, interpreting medical literature, and fulfilling academic tasks; encounter significant difficulties in contextual understanding, precise application, and pronunciation; and favor multimedia learning incorporating visual aids, interactive activities, and self-evaluation components. Instructors verified the absence of digital resources tailored to various disciplines that facilitate independent study. The results encourage the development of a mobile-compatible, multimedia-enhanced e-module to connect passive recognition with active application of medical terminology, promoting vocabulary proficiency and learner autonomy in English for Medical Purposes.